Curcumin Reduces Hepatic IL-6 Expression in an L-NAME–Induced Preeclampsia Model in Wistar Rats (Rattus norvegicus) - Mutiara Putri Nanda Rizki; Desy Aulina Sururi; Bambang Rahardjo; Tatit Nurseta (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Preeclampsia is a pregnancy complication after 20 weeks of gestation characterized by hypertension, proteinuria, and endothelial dysfunction driven by oxidative stress and inflammation. Elevated interleukin-6 (IL-6) contributes to hepatic injury and increases the risk of HELLP syndrome. Curcumin, the active compound of Curcuma longa, possesses antioxidant and anti-inflammatory effects via inhibition of the NF-κB pathway, potentially suppressing IL-6 expression in hepatic tissue. This study aimed to evaluate the effect of curcumin on hepatic IL-6 expression in an L-NAME–induced preeclampsia model in Wistar rats. A true experimental post-test-only control group design was used with 25 pregnant rats (n = 5/group) divided into a healthy control (K–), a disease model control (K+; L-NAME 125 mg/kg BW), and three curcumin-treated groups receiving 30, 50, and 100 mg/kg BW (P1, P2, P3). IL-6 expression in hepatic tissue was assessed immunohistochemically and quantified using ImageJ software. Data were normally distributed (Shapiro–Wilk p = 0.288) and homogeneous (Levene p = 0.277), allowing one-way ANOVA and Pearson correlation analyses (α = 0.05). Mean ± SD hepatic IL-6 expression (% area) was K– = 5.04 ± 2.32, K+ = 62.97 ± 2.71, P1 = 55.45 ± 2.57, P2 = 28.49 ± 4.08, and P3 = 16.46 ± 2.60 (p < 0.001, η² = 0.94). Post-hoc HSD analysis showed significant reductions in all curcumin-treated groups compared with K+, with the highest dose (P3) showing the greatest reduction and values approaching normal levels. A strong negative correlation (r = –0.962, p < 0.001; 95% CI = [–0.99, –0.86]) indicated a clear dose-related trend between curcumin administration and decreased IL-6 expression. These findings suggest that curcumin attenuates hepatic IL-6 expression in an L-NAME–induced preeclampsia model in a dose-related manner, supporting its potential hepatoprotective and anti-inflammatory roles against preeclampsia-associated oxidative injury. Keywords: Curcumin, Immunohistochemistry, Liver, L-NAME, Pregnancy